Rigidities and adjustments of daily prices to costs: Evidence from supermarket data (2020)
We assess the extent of inertia in grocery retail prices using data on prices and costs from a large supermarket chain in Colombia. Relative to previous work our analysis benefits from encompassing a wide variety of products, availability of reliable replacement cost data, and the daily frequency of the data. We confirm the existence of significant nominal rigidities in reference prices (three months) and even more so in reference costs (about six months), but differing depending on the type of product, being on average smaller in the case of perishable goods. Using a non-linear autoregressive distributed lag (NARDL) approach to cointegration, we examine the path of prices relative to costs and determine the speed of adjustment of prices to shocks. We find significant mean reversion but also uncover asymmetries in response to positive and negative changes in costs. As a novel finding, we uncover evidence of the effect of market concentration, input price volatility, along with own labels and the perishable nature of products, on the likelihood of price asymmetry in response to costs changes. © 2020